The residual life of bendiocarb on different substrates under laboratory and field conditions in Benin, Western Africa - Djènontin, Armel; Aïmihouè, Odile; SEZONLIN, MICHEL; Damien, Georgia; Ossè, Razaki A.; Soukou, Bhonna; Padonou, Gil; Chandre, Fabrice; Akogbéto, Martin C. (My University, 2013)
Background: The efficacy of bendiocarb against pyrethroid resistant An. gambiae and the residual life of this insecticide on different substrates were evaluated under laboratory and field conditions. Methods: Bioassays according to the WHO (World Health Organization) standard protocol were carried out on different substrates impregnated with bendiocarb. Data were analyzed using a binomial regression model with R software. Results: A good efficacy of the bendiocarb against pyrethroid resistant An. gambiae and a high variation of its residual life according to the surfaces treated was observed. The probability that a female mosquito died after exposure to a treated substrate was below 80% after 13 weeks for the teak wood; 7 weeks for the wall made with a mixture of sand and cement and 6 weeks for walls made with red clay and those made with a mixture of the red clay and cement. Conclusions: Considering the residual life of bendiocarb on walls made with red clay, the main substrates treated during IRS campaigns in rural areas in Benin, more than 2 treatments rounds per year would be necessary to achieve a long term efficacy of IRS using bendiocarb in these areas. Financial and logistical resources required to achieve such levels of coverage need more political will from leaders of African endemic countries. While waiting for innovative malaria control tool, alternative insecticides or combinations of insecticides have to be used for insecticide resistance management in Benin.
Keywords: Indoor residual spraying; Bendiocarb; Residual life; Substrates; Laboratory; Field